Examining the effectiveness of different dental recall strategies on maintenance of optimum oral health: the INTERVAL dental recalls randomised controlled trial - Clarkson, Jan E. (Br Dent J, 2021)
Objective To compare the clinical effectiveness of different frequencies of dental recall over a four-year period. Design A multi-centre, parallel-group, randomised controlled trial with blinded clinical outcome assessment. Participants were randomised to receive a dental check-up at six-monthly, 24-monthly or risk-based recall intervals. A two-strata trial design was used, with participants randomised within the 24-month stratum if the recruiting dentist considered them clinically suitable. Participants ineligible for 24-month recall were randomised to a risk-based or six-month recall interval. Setting UK primary dental care. Participants Practices providing NHS care and adults who had received regular dental check-ups. Main outcome measures The percentage of sites with gingival bleeding on probing, oral health-related quality of life (OHRQoL), cost-effectiveness. Results In total, 2,372 participants were recruited from 51 dental practices. Of those, 648 were eligible for the 24-month recall stratum and 1,724 participants were ineligible. There was no evidence of a significant difference in the mean percentage of sites with gingival bleeding on probing between intervention arms in any comparison. For those eligible for 24-month recall stratum: the 24-month versus six-month group had an adjusted mean difference of -0.91%, 95% CI (-5.02%, 3.20%); the 24-month group versus risk-based group had an adjusted mean difference of 0.07%, 95% CI (-3.99%, 4.12%). For the overall sample, the risk-based versus six-month adjusted mean difference was 0.78%, 95% CI (-1.17%, 2.72%). There was no evidence of a difference in OHRQoL (0-56 scale, higher score for poorer OHRQoL) between intervention arms in any comparison. For the overall sample, the risk-based versus six-month effect size was -0.35, 95% CI (-1.02, 0.32). There was no evidence of a clinically meaningful difference between the groups in any comparison in either eligibility stratum for any of the secondary clinical or patient-reported outcomes. Conclusion Over a four-year period, we found no evidence of a difference in oral health for participants allocated to a six-month or a risk-based recall interval, nor between a 24-month, six-month or risk-based recall interval for participants eligible for a 24-month recall. However, patients greatly value and are willing to pay for frequent dental check-ups. Zusatzmaterial online: Zu diesem Beitrag sind unter 10.1038/s41415-021-2612-0 für autorisierte Leser zusätzliche Dateien abrufbar.